Is intracytoplasmic morphologically selected sperm injection (IMSI) beneficial in the first ART cycle? A multicentric randomized controlled trial. (21st June 2013) - Leandri, R. D.; Gachet, A.; Pfeffer, J.; Celebi, C.; Rives, N.; Carre‐Pigeon, F.; Kulski, O.; Mitchell, V.; Parinaud, J.
Summary: Intracytoplasmic morphologically selected sperm injection (IMSI), by selecting spermatozoa at high magnification improves the outcome of intracytoplasmic sperm injection (ICSI) mainly after several failures. However, only few monocentric randomized studies are available and they do not analyse results as a function of sperm characteristics. In 255 couples attempting their first assisted reproductive technology (ART) attempt for male infertility (motile sperm count <1×10 6 after sperm selection, but at least 3×10 6 spermatozoa per ejaculate to allow a detailed analysis of sperm characteristics), a prospective randomized trial was performed to compare the clinical outcomes of IMSI and ICSI and to evaluate the influence of sperm characteristics on these outcomes. IMSI did not provide any significant improvement in the clinical outcomes compared with ICSI neither for implantation (24% vs. 23%), nor clinical pregnancy (31% vs. 33%) nor live birth rates (27% vs. 30%). Moreover, the results of IMSI were similar to the ICSI ones whatever the degree of sperm DNA fragmentation, nuclear immaturity and sperm morphology. These results show that IMSI instead of ICSI has no advantage in the first ART attempts. However, this does not rule out IMSI completely and more randomized trials must be performed especially regarding patients carrying severe teratozoospermia, or high sperm DNA fragmentation levels or having previous ICSI failures.